Pentagonal Resistensi: Faktor Penyebab Rendahnya Implementasi Akuntansi Pada UMKM - Suryantara, Adhitya Bayu; Ridhawati, Rini (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2023)
MSMEs face obstacles that usually occur in business, the limitations of making financial reports. Limited accounting knowledge makes it difficult for MSMEs to determine the policies to be taken. This research uses an exploratory method to explore the causes of the low implementation of accounting by MSME actors. The informants in this study were owners or financial controllers of 10 MSMEs in the East Lombok Regency. Data collection techniques using interviews and observation are analyzed using transcribing, information reduction, codification, data visualization, and results analysis. The results of the study show that MSMEs think the preparation of accounting reports according to standards has not provided benefits for them. The compilation of reports according to standards is only carried out if there are demands related to capital assistance. MSMEs agree that records are important, and they make records based on a format adapted to the information they need. The five factors, namely educational background, accounting complexity, business size, relations with outsiders, and training received, contributed to building the perceptions of MSME actors in interpreting, compiling, and utilizing their company's accounting information